Effect of Moisture Content on Resistance to Airflow of Oilseeds - Pandiarajan, T; Sreenarayanan, V V (Journal of Agricultural Engineering, 2003)
The flow resistances of sunflower and soybean in the air flow range of 1.85 to 6.02 mÂ³/mÂ².s were determined under laboratory conditions. The effect of moisture content on the resistance to airflow was quantified. Shedd’s equation described the air flow resistance data well. The resistance to airflow decreased with an increase in seed moisture content for both oilseeds.